The Global Race for Technological Superiority Discover the Security Implications - Fabio Rugge (Pubblicazioni ISPI, 2020)
This report published by ISPI and the Brookings Institution analyzes the challenges to international order posed by the ongoing race for technological superiority. From artificial intelligence and quantum computing to hypersonic weapons and new forms of cyber and electronic warfare, advances in technology have threatened to make the international security environment more unpredictable and volatile - yet the international community remains unprepared to assess and manage that risk. What is needed is a mature understanding of how technology has emerged as a key enabler of sovereignty in the XXI century, how the ongoing race for technological supremacy is disrupting the balance of power globally, and what the attendant strategic and security implications of those transformations will be. This report is an effort to that end.